1995
DOI: 10.1111/j.1532-5415.1995.tb07004.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resistance Training on Strength, Power, and Selected Functional Abilities of Women Aged 75 and Older

Abstract: Progressive resistance exercise can produce substantial increases in muscle strength and in power standardized for body weight in healthy, very old women. However, isolated increases in strength and LEP/kg may confer only limited functional benefit in healthy, independent, very old women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
231
5
17

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(269 citation statements)
references
References 25 publications
(39 reference statements)
15
231
5
17
Order By: Relevance
“…Finally, the two training programmes employed in the present study appear to have enhanced habitual function, more successfully than previous studies' attempts to do so, particularly where the get-upand-go test is concerned (Earles et al 2001;Fiatarone et al 1990;Schlicht et al 2001;Skelton et al 1995). Nevertheless, our findings of improved function with training do corroborate with the findings of some earlier studies (Skelton et al 1997;Taaffe et al 1999), even where the lower intensity group is concerned.…”
Section: Functional Abilities Changes With Exercise Trainingsupporting
confidence: 64%
See 1 more Smart Citation
“…Finally, the two training programmes employed in the present study appear to have enhanced habitual function, more successfully than previous studies' attempts to do so, particularly where the get-upand-go test is concerned (Earles et al 2001;Fiatarone et al 1990;Schlicht et al 2001;Skelton et al 1995). Nevertheless, our findings of improved function with training do corroborate with the findings of some earlier studies (Skelton et al 1997;Taaffe et al 1999), even where the lower intensity group is concerned.…”
Section: Functional Abilities Changes With Exercise Trainingsupporting
confidence: 64%
“…The tests of functional ability were all performed on 1 day at the outset and completion of the study and were similar to a battery of functional tests performed by participants in previous research (Chandler et al 1998;Skelton et al 1995).…”
Section: Functional Abilities Measuresmentioning
confidence: 99%
“…Despite HGS not differing by level of physical activity, regardless of lateral dominance, the results show a clear upward trend of strength as individuals move from the inactive group to the active. According results found by Skelton et al, 29 in an intervention study, a significant improvement in HGS was found in the group of active elderly persons compared to the group that did not undergo the intervention. The elderly who belonged to the active group underwent a program consisting of resistance exercises for a period of three months, three times a week.…”
Section: Discussionsupporting
confidence: 49%
“…These results are, however, in line with previous studies hypothesizing that decreased lower extremity muscle power may be the key factor in age-related decline of physical performance (Runge et al 2004) and functional capacity (Bassey et al 1992;Bean et al 2003;Yamauchi et al 2010). Muscle power is lower in older individuals, the decline in maximal power takes place before failure in muscle strength (Skelton et al 1995) and is greater than in muscle strength (Häkkinen et al 1998;Macaluso and De Vito 2004). Lower extremity muscle power has also been shown to be a performance-based function, which is assumed to be caused by the fact that daily living tasks such as walking or rising from a chair are dynamic movements that require power production (Aalund et al 2013).…”
Section: Discussionmentioning
confidence: 99%